Undergraduate student mental health at Makerere University, Uganda - Ovuga, Emilio; Boardman, Jed; Wasserman, Danuta (World psychiatry, 2006)
There is little information on the current mental health of University students in Uganda. The present study was carried out to determine the prevalence of depressed mood and suicidal ideation among students at Makerere University. Two student samples participated. Sample I comprised 253 fresh students admitted to all faculties at the University in the academic year 2000/2001, selected by a simple random sampling procedure. Sample II comprised 101 students admitted to the Faculty of Medicine during the academic year 2002/2003. The prevalence of depressed mood was measured using the 13-item Beck Depression Inventory (BDI). The prevalence of depressed mood (BDI score 10 or more) was significantly higher in sample I (16.2%) than sample II (4.0%). Sample I members were significantly more likely than those of sample II to report lifetime and past week suicide ideation. Thus, there is a high prevalence of mental health problems among the general population of new students entering Makerere University and this is significantly higher than for new students in the Faculty of Medicine.
Keywords: Students; Mental health problems; Depressed mood; Suicidal ideation